Oriented nucleation in formamidinium perovskite for photovoltaics - YAVUZ, İLHAN (My University, 2023)
The black phase of formamidinium lead iodide (FAPbI3) perovskite shows huge promise as an efficient photovoltaic, but it is not favoured energetically at room temperature, meaning that the undesirable yellow phases are always present alongside it during crystallization1–4. This problem has made it difficult to formulate the fast crystallization process of perovskite and develop guidelines governing the formation of black-phase FAPbI3(refs.5,6). Here we use in situ monitoring of the perovskite crystallization process to report an oriented nucleation mechanism that can help to avoid the presence of undesirable phases and improve the performance of photovoltaic devices in different film-processing scenarios. The resulting device has a demonstrated power-conversion efficiency of 25.4% (certified 25.0%) and the module, which has an area of 27.83 cm2, has achieved an impressive certified aperture efficiency of 21.4%.
Keywords: Temel Bilimler; Natural Sciences; Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; MULTIDISCIPLINARY SCIENCES; Multidisipliner; Multidisciplinary